Persepsi peternak terhadap faktor-faktor yang mempengaruhi pendapatan usaha ternak sapi potong di desa Ciro-Ciroe Kabupaten Sidenreng Rappang - Uni, Sri Wahyuni; Nugraha, Angga; Purnomo, Nurul (Universitas Islam Balitar, 2025)
This study aims to identify the factors influencing the income of beef cattle farming businesses in Ciro-ciroe Village, Watang Pulu District, Sidenreng Rappang Regency. The research employs a quantitative method with a sample size of 17 respondents. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS 16.0 for Windows. The results show that the feed variable (X1) has a significance value of 0.029 < 0.05, maintenance management (X2) is 0.048 < 0.05, and livestock health (X4) is 0.027 < 0.05. This indicates that these three variables have a significant effect on the income of beef cattle farmers. Meanwhile, the marketing variable (X3) has a significance value of 0.451 > 0.05, indicating no significant effect on income. Simultaneously, the F-test results show a significance value of 0.001 < 0.05, which means that all four variables collectively have a significant influence on the income of beef cattle farming businesses.